The study of analysis characterization in “five feet apart” movie by justin baldoni - Maharani, Ni Putu Ayu Gita; Putra, I GB Wahyu Nugraha; Aryaningsih, Ni Nyoman Deni (Journal of Language and Applied Linguistics, 2022)
This study is focused on analyzing characterization in “Five Feet Apart “movie by Justin Baldoni. This study has two aims, namely 1) to find out the types of characterization and to describe the main character in “Five Feet Apart” and 2) to find out the characterization of the main character realized in “Five Feet Apart” movie by Justin Baldoni. The data were analyzed based on the theory proposed by Kenney (1996) and Wellek and Warren (1962). The result of this analysis showed that there were 5 types of characterization from Kenney theory such as Discursive Method, Dramatic Method, Character on other Character, Mixing Method and Contextual Method and 3 theory dimension characterization such as Physiological Dimension, Sociological Dimension and Psychological Dimension.